(untitled) (Revista do Centro de Estudos Portugueses, 2011)
Este artigo analisa “Cismar”, de Álvares de Azevedo, investigando as soluções formais encontradas pelo poeta para dar expressão ao conteúdo ideacional do poema This article analyzes Álvares de Azevedo’s poem entitled “Cismar”, investigating the formal techniques employed by the poet to convey the work’s main ideas.